Identification and characterization of miRNAs expressed in the bovine ovary - Tholen Ernst; Phatsara Chirawath; Rings Franca; Hoelker Michael; Ghanem Nasser; Hossain Md; Schellander Karl; Tesfaye Dawit (BMC Genomics, 2009)
Abstract Background MicroRNAs are the major class of gene-regulating molecules playing diverse roles through sequence complementarity to target mRNAs at post-transcriptional level. Tightly regulated expression and interaction of a multitude of genes for ovarian folliculogenesis could be regulated by these miRNAs. Identification of them is the first step towards understanding miRNA-guided gene regulation in different biological functions. Despite increasing efforts in miRNAs identification across various species and diverse tissue types, little is known about bovine ovarian miRNAs. Here, we report the identification and characterization of miRNAs expressed in the bovine ovary through cloning, expression analysis and target prediction. Results The miRNA library (5'-independent ligation cloning method), which was constructed from bovine ovary in this study, revealed cloning of 50 known and 24 novel miRNAs. Among all identified miRNAs, 38 were found to be new for bovine and were derived from 43 distinct loci showing characteristic secondary structure. While 22 miRNAs precursor loci were found to be well conserved in more than one species, 16 were found to be bovine specific. Most of the miRNAs were cloned multiple times, in which let-7a, let-7b, let-7c, miR-21, miR-23b, miR-24, miR-27a, miR-126 and miR-143 were cloned 10, 28, 13, 4, 11, 7, 6, 4 and 11 times, respectively. Expression analysis of all new and some annotated miRNAs in different intra-ovarian structures and in other multiple tissues showed that some were present ubiquitously while others were differentially expressed among different tissue types. Bta-miR-29a was localized in the follicular cells at different developmental stages in the cyclic ovary. Bio-informatics prediction, screening and Gene Ontology analysis of miRNAs targets identified several biological processes and pathways underlying the ovarian function. Conclusion Results of this study suggest the presence of miRNAs in the bovine ovary, thereby elucidate their potential role in regulating diverse molecular and physiological pathways underlying the ovarian functionality. This information will give insights into bovine ovarian miRNAs, which can be further characterized for their role in follicular development and female fertility as well.